Analisis Kinerja Aparatur Sipil Negara di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Kepahiang - Riska Handayani; Titi Darmi; Rosidin (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2022)
Human Resources (HR) is very important for an organization. Because the success of an organization in improving its performance is dependent on the quality of operating human resources. If employees have a good performance, then they can solve all organizational burdens effectively and efficiently so that problems that occur in the organization can be resolved properly. This research is a descriptive research with a qualitative approach. Informants were determined by purposive sampling technique as many as 5 informants. The data sources consist of primary data and secondary data. The data collection technique was carried out by means of observation, interviews, and documentation. The data analysis technique used by the researcher went through the stages of data reduction, data presentation, and drawing conclusions. Data validation technique is done by triangulation. The triangulation used by the researcher is source triangulation and method triangulation. The results of this study indicate that the performance of the State Civil Apparatus at the Department of Population and Civil Registration of Kepahiang Regency has been going well, in accordance with the applicable laws and regulations. The services they provide are because there are no residents who complain about the slow process of printing E-KTP, Birth Certificates, and Family Cards. The printing process is carried out since the required files are declared complete, and there are no additional requirements in the administration of population administration. There is also no problem with the service queue number, there has never been a service queue number running out.